Integrating entrepreneurial education into early childhood and care education in Nigeria (2011)
Entrepreneurial education is increasingly considered valuable in every society that desires steady economic growth. Most Nigeria graduates as at today are job seekers instead of job creators. This results from emphasis on certification rather than productivity and relevance to the needs of the society after graduation. This paper therefore examines the areas of Early Childhood Care Education programme in Nigeria into which entrepreneurial education can be integrated in order to make the products of the programme productive, relevant and self-reliant. It is recommended among other things that Nigerian government should begin to develop entrepreneurial thinking through legislation that will promote entrepreneurial education. This will ultimately make education to play its role in the achievement of vision 2020 in Nigeria.